2009
DOI: 10.1007/s00415-009-5178-3
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and barriers to clinical practice guidelines in general and to the guideline on Parkinson’s disease. A National Survey of German neurologists in private practice

Abstract: Although much progress has been made in the development of clinical practice guidelines (CPGs), there are few strategies for dissemination and implementation of these guidelines. This study examines the attitudes of neurologists to CPGs and barriers to CPG implementation, with a particular focus on the Parkinson's disease CPG (PD-CPG). A cross-sectional survey was performed in 2007 with a representative sample of 213 neurologists in private practice in Germany. The main outcome measures were the Tunis Attitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
(42 reference statements)
3
33
1
1
Order By: Relevance
“…Compared to both international and Swiss studies and reviews, we found even more favorable attitudes (Table 2). 6,7,9,14,15,23 Particularly striking in this regard was the disagreement with statements about guidelines being oversimplified, too rigid to apply to individual patients, and a challenge to physician autonomy: these beliefs were shared by less than 15% of the participants. This result may be due to fewer medico-legal and regulatory concerns regarding guidelines threatening physician autonomy in Switzerland than in other countries (eg, US).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to both international and Swiss studies and reviews, we found even more favorable attitudes (Table 2). 6,7,9,14,15,23 Particularly striking in this regard was the disagreement with statements about guidelines being oversimplified, too rigid to apply to individual patients, and a challenge to physician autonomy: these beliefs were shared by less than 15% of the participants. This result may be due to fewer medico-legal and regulatory concerns regarding guidelines threatening physician autonomy in Switzerland than in other countries (eg, US).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the assessment that only 57% of the physicians in the IG and 50% of the physicians in the CG believe that the CPG-PD improves the treatment in the clinical setting. A previous survey of the authors concerning attitudes and barriers to the CPG-PD performed in 2007 even revealed a lower ratio of only 29% of neurologists in private practice thinking that the CPG-PD enhances the [13]. Other studies [2, 10, 32] also reported low impact on practice changes although the physicians agreed to be better prepared after intensive guideline implementation.…”
Section: Discussionmentioning
confidence: 75%
“…Two surveys [13,21] showed that neurologists in private practice have a positive attitude to CPGs in general and a high level of awareness of the CPG-PD (88%), but that the estimated impact of CPGs on the quality of care is low. Data of the impact of the CPG-PD on the process and outcome of health care in PD patients are still missing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Larisch and colleagues studied neurologists' attitudes towards clinical guidelines and barriers to their implementation [5]. Response rate in this questionnaire survey was low (around 20%) but 213 neurologists were included in the analysis.…”
Section: Diagnosismentioning
confidence: 99%